2022
DOI: 10.1039/d2ra03763g
|View full text |Cite
|
Sign up to set email alerts
|

Indirect aqueous carbonation of CaSO4·2H2O with aspartic acid as a recyclable additive

Abstract: Aspartic acid was employed as a recyclable additive during the indirect aqueous carbonation of CaSO4·2H2O. The multiple roles of aspartic acid were found to be Ca2+ leaching agent, CO2 absorbent, and CaCO3 polymorph regulator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Next, CO 2 was passed through the calcium-rich solution to form calcium carbonate and complete the CO 2 sequestration. Finally, the leaching agent was regenerated and recycled [53][54][55]. The technical process is shown in Figure 2, corresponding to reaction Equations ( 1)-(3).…”
Section: Chemical Composition Of Industrial By-product Gypsum and Pri...mentioning
confidence: 99%
See 2 more Smart Citations
“…Next, CO 2 was passed through the calcium-rich solution to form calcium carbonate and complete the CO 2 sequestration. Finally, the leaching agent was regenerated and recycled [53][54][55]. The technical process is shown in Figure 2, corresponding to reaction Equations ( 1)-(3).…”
Section: Chemical Composition Of Industrial By-product Gypsum and Pri...mentioning
confidence: 99%
“…Gong et al [55] leached and mineralized CaSO 4 •2H 2 O by exploiting the solubility difference of aspartic acid at different pH values. The results showed that the solubility of CaSO 4 •2H 2 O was 16.3 g L −1 in 7 wt.% ammonia and a liquid-to-solid ratio of 50.…”
Section: Complexationmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction between Asp molecules and calcium has been widely investigated from the perspective of surface energy [ 13 ] and kinetics [ 14 ], but the actual mechanism is still not that clear. One generally accepted fact is that there exists a complexation effect between Asp molecules and calcium ions [ 15 ], and some functional groups like -COO - could serve as potential nucleation sites for the crystallization of CaCO 3 [ 16 ]. Recent studies show that Asp may also bind to the precipitated crystals [ 17 ] and affect the morphology, phase, and crystal structure through the additional electrostatic interactions of side-chain groups with mineral surfaces [ 18 ].…”
Section: Introductionmentioning
confidence: 99%